Serum apoprotein A1 levels are inversely associated with disease activity in gout: From a southern Chinese Han population. Issue 17 (April 2017) - Huang, Heqing; Yu, Bing; Liu, Wen; Lin, Qingyan; Chen, Liying; Chen, Juan; Duan, Lihua; Shi, Guixiu
Abstract : Abstract: To analyze the alteration of lipid profile and inflammatory markers in the serum of patients with gouty arthritis (GA), the levels of serum lipid profile, C-reactive protein (CRP), and erythrocyte sedimentation rates (ESRs) were measured in the serum of 69 gout patients, 35 patients with rheumatoid arthritis (RA), 23 patients with ankylosing spondylitis (AS)/spondyloarthropathy (SpA), and 25 patients with osteoarthritis (OA). The serum levels of apoprotein A1 (Apo-A1) were significantly decreased in patients with gout when compared with RA, AS/SpA, and OA patients. The serum levels of CRP were significantly increased in gouty patients when compared with RA, AS/SpA, and OA patients. Furthermore, the serum levels of ESR were significantly increased in patients with gout compared to patients with OA. Correlation analysis indicated that the levels of Apo-A1 were negatively correlated with serum ESR and CRP ( r  = −0.475, P  < .001; r  = −0.380, P  = .001, respectively) in the patients with GA. Taken together, this study gives us a better understanding of the relationships between serum lipid profile and inflammatory markers in gout patients.